Mediating effect of uncertainty on relationship between interpersonal attraction traits and life happiness amongst facebook users - Attan, Sri Azra (2019)
The most influential factor that affects the potential of individual fulfilment is interpersonal attraction; a perception of being attractive and feeling attracted towards another. Although social media, e.g. Facebook, offers an alternative for Face-to-Face (FtF) interaction by reading news and updates, Mediated-Communication users tend to post more negative items, which undesirably affected their happiness in life. This makes interpersonal attraction in cyberspace is more challenging compared to FtF environment. Since interpersonal attraction is developed during the initial interaction, there is a large amount of uncertainty that needs to be assured to experience happiness in life. The limitation of previous studies is when the scholars were only focusing on the direct effect of interpersonal attraction on life happiness. Thus, there should be a mediating variable to strengthen the relationship between interpersonal attraction and life happiness. Hence, this study examined the mediating effect of uncertainty on relationship between interpersonal attraction traits, namely physical attraction, social attraction, extraversion and popularity towards life happiness amongst Facebook users. A quantitative survey was conducted by distributing a set of a questionnaire via a survey-development website to 402 Facebook users who were selected through snowball sampling technique. It was found that as more physical attraction, social attraction and extraversion are shown by other Facebook users; the lower the uncertainty, the higher the life happiness. However, as more popularity is shown by other Facebook users; the lower the uncertainty, however, it is not enhancing the life happiness. The role of mediated-communication is a new perspective of the predicament in the communication field since this study contributed to a worthier understanding of online human behaviour.